1992
DOI: 10.1177/105381519201600302
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Parental Knowledge to the Development of Extremely Low Birth Weight Infants

Abstract: This study examined the relationship between parental experience, parental knowledge, and the development of extremely low birth weight infants. The subjects (Ti = 40) were extremely high-risk infants averaging 1000.0 grams birthweight and 28.1 weeks gestational age. The study found that mothers of preterm infants called upon the same types of experiences and sources of information about infancy as mothers of full-term infants. Further, ratings of maternal accuracy on the Knowledge of Infant Development Invent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
68
2
4

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(78 citation statements)
references
References 16 publications
2
68
2
4
Order By: Relevance
“…Given the country's great wealth and rapid economic growth, opportunities should be made available for parents, in general, and mothers, in particular, to be educated about typical child development and effective parenting practices. Previous research studies in this specific area of research have shown quite clearly that mothers with adequate knowledge of child development are more likely to interact with their children in more sensitive ways and adopt parenting strategies that tend to promote their children's development and well-being (Dichtelmiller et al, 1992;Goodnow, 1988;Miller, 1988;Sigel, 1992). Additionally, lack of adequate information about child development displayed by mothers in this study has important implications for clinical practice.…”
Section: Implications For Couple and Family Practicementioning
confidence: 99%
See 1 more Smart Citation
“…Given the country's great wealth and rapid economic growth, opportunities should be made available for parents, in general, and mothers, in particular, to be educated about typical child development and effective parenting practices. Previous research studies in this specific area of research have shown quite clearly that mothers with adequate knowledge of child development are more likely to interact with their children in more sensitive ways and adopt parenting strategies that tend to promote their children's development and well-being (Dichtelmiller et al, 1992;Goodnow, 1988;Miller, 1988;Sigel, 1992). Additionally, lack of adequate information about child development displayed by mothers in this study has important implications for clinical practice.…”
Section: Implications For Couple and Family Practicementioning
confidence: 99%
“…Parenting programs designed to increase maternal knowledge and promote effective parenting practices produced positive developmental outcomes (Benasich & Brooks-Gunn, 1996;Dichtelmiller et al, 1992;Miller, 1988). Maternal knowledge of child development has been studied extensively over the past decades, and, in general, research has revealed strong positive relationships between knowledge of child development and the demographic characteristics of the mother (Benasich & BrooksGunn, 1996;Bornstein, Cote, Haynes, Hahn, & Park, 2010;Brooks-Gunn & Furstenberg, 1986;Reich, 2005;Richman, Miller, & LeVine, 1996; AQ 1 Roosa, 1983).…”
Section: Mothers' Demographic Characteristics and Knowledge Of Child mentioning
confidence: 99%
“…The KIDI is a widely used measure of knowledge of children's development, 3,10,43,44 and it is used in the Early Head Start Research and Evaluation Project, currently being conducted by the Administration for Children and Families, US Department of Health and Human Services. The KIDI is also related to another widely used measure of mothers' knowledge of children's development: the Concepts of Development Questionnaire (CODQ) (ie, the KIDI was significantly positively related to the Perspectivistic subscale of the CODQ and significantly negatively related to the Categorical subscale of the CODQ 7 ).…”
Section: Instrumentsmentioning
confidence: 99%
“…양육지식과 양육행동 간의 관계를 살펴본 Lee ( (Dichtelmiller, et al, 1992). 또한 어머니가 양육에 대한 지식을 많이 가질수록 어머니는 양육에 대한 효능감이 높 으며, 양육에 대해 더 많이 만족하는 것으로 나타났다 (Bornstein et al, 2003.…”
unclassified
“…이 뿐만 아 니라 어머니가 양육에 대한 지식을 많이 가질수록 더 적 절한 양육의 기술을 구사하며 (Stevens, 1984) (Hong & Kim, 2008;Lee & Lee, 2010;Shim, et al, 2007;Yang & Cho et al, 2009)가 대부분이며, 양육지식의 양육행동과 양육효능감 에 대한 영향 연구 (Lee, 2009; (Ahn & Park, 2002;Park, et al, 1996;Shin, 1997), 비일관적인 훈육을 하기도 하는 것으로 보고되고 있으며 (Lempers, et al, 1989), 양육스트레스가 낮을수록 자녀를 합리적으로 지도하고 애정적으로 대하는 것으로 보고되고 있다 (Kim & Moon, 2005). 특히 어머니의 양육스트레스 는 지속적인 특성이 있어 그 특성이 크게 변화하지 않고, 유아가 발달하는 동안에도 유아의 부적응이나 문제행동에 직접적으로 또는 간접적으로 영향을 주며 (Crinic, et al, 2005), 유아의 대인적응성, 인기도/지도력과 같은 사회성 발달에도 영향을 준다고 한다 (Kim & Do, 2004 (Bornstein, 2003;Dichtelmiller, et al, 1992;Donovan, et al, 2007) (Ainsworth, et al, 1978;Kim & Park, 2008;Lasko, et al, 1999). …”
unclassified